From Viral to Ijab Kabul: The Role of Social Media in Driving Child Marriage - Sri Nanang Meiske Kamba (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2026)
This study examines the phenomenon of child marriage in the context of digital transformation, focusing on the role of social media as a new factor influencing the practice of marriage dispensation in Indonesia. In contrast to the classic approach that focuses on economic, cultural, and educational factors, this study highlights how social media algorithms and virality phenomena shape the social pressures that drive child marriage decisions. This study uses normative legal methods with a critical approach, supported by a limited conceptual and socio-legal approach to analyze the interaction between legal norms and digital reality. The results of the study show that the emergence of digital moral panic and the dominance of digital public opinion has shifted the basis of the legitimacy of child marriage from legal considerations to algorithm-based social pressure. In addition, the digital public is transforming into informal legal actors that influence family decisions and judicial practices. This condition causes distortions of the principles of child protection and maqasid al-shari'ah. Therefore, a reformulation of a legal approach that is adaptive to technological developments is needed.